Head Teachers' Leadership on SIP Preparation: A Study of Community Schools in Kirtipur Municipality, Kathmandu (Interdisciplinary Research in Education, 2025)
This research examines the school improvement planning practices of school head teachers to address general issues in their regular school leadership processes. It examines the plans schools develop to conduct their daily activities and the procedures they adopt to address them. As qualitative research, it is based on the existing experiences of head teachers. The purposively selected three head teachers were interviewed in a semi-structured approach, and their responses were recorded, and a transcription was done to build common themes. The common themes were elaborated with appropriate verbatim to refer to further evidence. From the experiences of head teachers, the findings analyzed include the following: schools perceive SIP as the sole document for school development; however, it has dominantly restricted head teachers from going beyond. Head teachers don’t initiate the preparation of other broad proposals or concept notes for exploring external funds to enlarge school capacity. But for short-term purposes, the school prepares a few periodical plans, including an annual academic calendar. Head teachers encourage collaborative work of team members in formulating such short-term plans; they also use their intuitive wisdom to address the issues approached in the general school administration process.